Clinical Comparison of Dental Caries by DMFT and ICDAS Systems - Sepideh Banava; Melika Fattah; Mohammad javad Kharrazifard; Tahmineh Safaie; Shima Askarzadeh; Mohammad Safaie Yazdi; Banet .T. Amaechi; Mahta Fazlyab (Islamic Dental Association of Iran, 2012)
Background and Aim : The common method of caries status evaluation is the number of decayed, missed and filled teeth (DMFT) index. Recently the International Caries Diagnosis and Assessment System (ICDAS) has been introduced for a detailed evaluation of the dental caries. The aim of this study was to evaluate the caries status with this new system while comparing it with the DMF index as a common method .   Materials and Methods : A total of 110 dental students were selected randomly and examined. Examination was done in the dental unit under good light circumstances. First, all surfaces of the teeth were cleaned with a brush, rubber cup and prophylaxis paste and then rinsed. Subsequently, examination was performed in each person by two calibrated examiners according to DMFT system and ICDAS (evaluation of teeth status in occlusal and smooth surfaces in dry and wet situations according to codes of this system) and the information forms were completed. Chi square statistical test was used for data analysis .   Results : The mean DMFT was 7.16. According to ICDAS system nobody had 00 code meaning that at least one surface of 182 dental surfaces had a lesion. Only seven cases had codes 00-02. The results for codes 03 through 06 were as follow, respectively: 51, 49, 34, 2. Ninety nine cases had extracted or non-examinable teeth. The inter-examiner kappa coefficient was 0.916 .   Conclusion : The new system, ICDASl, provides more accurate information than DMF for the investigators and epidemiologists. The DMFT number does not show any details about the dental status of the cases .